Phase development in ZnO varistors. (January 2015) - Fan, J.; Poosimma, P.; Freer, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Based on a typical ZnO varistor composition (97·0 mol.-% ZnO, 1·0 mol.-% Bi2O3, 1·0 mol.-% Sb2O3, 0·5 mol.-% MnO and 0·5 mol.-% Co3O4), phase development of the ZnO varistor during sintering has been investigated using in situ high temperature X-ray diffraction up to 900°C, and conventional ambient X-ray diffraction for samples sintered at 900°C to 1250°C. The results indicate that α-Bi2O3 can be detected until 700°C; the pyrochlore phase can be detected in the samples heat treated at 700°C and up to 1250°C; the spinel phase is present at and >900°C. However, the main phases in the varistor are established by 950°C. By this temperature, the essential microstructure features are formed, and the varistors exhibit non-linear electrical properties, with a non-linear coefficient α of 35 and breakdown field of 8000 V cm−1. With increasing sintering temperature, both the α value and breakdown field decrease.